v-cbl, an oncogene from a dual-recombinant murine retrovirus that induces early B-lineage lymphomas. - Langdon, W Y (1989)
Cas NS-1 is an acutely transforming murine retrovirus that induces pre-B and pro-B cell lymphomas. Molecular cloning showed it was generated from the ecotropic Cas-Br-M virus by sequential recombinations with endogenous retroviral sequences and a cellular oncogene. The oncogene sequence shows no homology with known oncogenes but some similarity to the yeast transcriptional activator GCN4. A 100-kDa gag-cbl fusion protein, with no detectable kinase activity, is responsible for the cellular transformation. The cellular homologue of v-cbl, present in mouse and human DNA, is expressed in a range of hemopoietic lineages.